Development of 10 kW Three-Phase Grid Connected Inverter - Isen, Evren; Bakan, A. Faruk (KOREMA, 2016)
In this paper, modeling, simulation and experimental study of a 10 kW three-phase grid connected inverter are presented. The mathematical model of the system is derived, and characteristic curves of the system are obtained in MATLAB with m-file for various switching frequencies, dc-link voltages and filter inductance values. The curves are used for parameter selection of three-phase grid connected inverter design. The parameters of the system are selected from these curves, and the system is simulated in Simulink. Modeling and simulation results are verified with experimental results at 10 kW for steady state response, at 5 kW for dynamic response and at -3.6 kVAr for reactive power. The inverter is controlled with Space Vector Pulse Width Modulation technique in d-q reference frame, and dSPACE DS1103 controller board is used in the experimental study. Grid current total harmonic distortion value and efficiency are measured 3.59% and 97.6%, respectively.
Keywords: Grid Connected Inverter; Inverter Modeling; Space Vector Pulse Width Modulation; Total Harmonic Distortion; POWER; SYNCHRONIZATION; INTERFACE; Automation & Control Systems; Engineering